ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN STRUKTUR MODAL PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EEFEK INDONESIA TAHUN 2021-2023 - Anggraini Syahputri; Debi Eka Putri; Nelly Ervina; Hendrick Sasimtan Putra (Strategic: Journal of Management Sciences, 2025)
This study aims to analyze the effect of asset structure and profitability on capital structure in plastic and packaging companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Capital structure serves as the dependent variable, while asset structure and profitability are the independent variables. The population in this study includes all plastic and packaging companies listed on the Indonesia Stock Exchange, with a sample of 13 companies selected using purposive sampling. Data were obtained through documentation of annual financial reports and analyzed using multiple linear regression analysis. The results show that asset structure has no significant effect on capital structure, with a significance value of 0.701 (> 0.05). In contrast, profitability has a negative and significant effect on capital structure, with a significance value of 0.050 (= 0.05). These findings indicate that companies with higher profitability tend to rely more on internal financing rather than debt.